GP-survey 1985-1994 - Johansson, Bengt (University of Gothenburg, 1998)
The GP-survey is part of the MEDOFF-project (Media and the public sector) and an important issue for the project was the introduction of district committees (stadsdelsnämnder) in Göteborg and its effect on the local news coverage in media.

The GP-survey is part of the MEDOFF-project (Media and the public sector) and an important issue for the project was the introduction of district committees (stadsdelsnämnder) in Göteborg and its effect on the local news coverage in media.
GP-studien 1985-1994
Keywords: Media; Media; Social Sciences; Samhällsvetenskap; Media and Communication Studies; Medie- och kommunikationsvetenskap